The Influence of Entrepreneurial Characteristics on the Performance of Tourism Vlogger Entrepreneurs - Xie, Qing; Liu, Lisha; Malik, Haider; Chupradit, Supat; Chupradit, Priyanut Wutti (Frontiers in Psychology, 2021)
The current internet revolution has changed the entrepreneurial opportunities and trends. This study explores the relationship between the entrepreneurial characteristics (Innovation, Leadership, Planning, and Sociability) and the performance of vloggers entrepreneurs in India. Also, this study considers the mediating effect of entrepreneurial intentions. This study is cross-sectional in nature and considered 128 vlogger entrepreneurs for analysis. Smart-PLS was used to estimate SEM analysis for reliability and validity estimation along with path relationship. The findings are well important as the entrepreneurial characteristics can meaningfully predict the performance of vlogger entrepreneurs in positive direction. Moreover, the relationship between entrepreneurial characteristics and performance of entrepreneurs is partially mediated by entrepreneurial intentions. These findings have important implications for vloggers in Indian or similar nature countries. This study also put some future research directions at the end.